P956Improved quality of life and symptomatic atrial fibrillation reduction in patients treated with a standardized ablation index workflow. (18th June 2020) - Gupta, D; Vijgen, J; De Potter, T; Scherr, D; Van Herendael, H; Knecht, S; Kobza, R; Berte, B; Sandgaard, N; Albenque, J; Szeplaki, G; Stevenhagen, Y; et al.
Abstract: Background/Introduction: The use of a standardized 'CLOSE' ablation workflow for pulmonary vein isolation (PVI), with defined inter-tag distance (ITD) with targeted ablation index (AI) values, has been shown in single centre reports to result in good outcomes. The effect of this approach on patients' quality of life (QoL) has not been studied. Purpose: To evaluate the effects of paroxysmal atrial fibrillation (PAF) ablation by the CLOSE workflow on QoL and symptomatic AF reduction in the multicenter VISTAX study. Methods: 329 patients with PAF (61.5% male, 61.3 ± 10.1 year) were treated at 17 European centres by point-by-point radiofrequency ablation using the CLOSE protocol to achieve PVI.  An ITD ≤6mm and AI values of ≥400 on the posterior wall and ≥550 on the anterior wall were targeted. The AI value on the posterior wall was lowered as per investigator discretion in case of safety concerns. Patients were monitored for atrial arrhythmia recurrences via weekly and symptom-activated transtelephonic monitoring (TTM), for 12 months post procedure. Patients completed an Atrial Fibrillation Effect on Quality-of-life (AFEQT) questionnaire at their baseline and 12-month follow up visits. Results: Majority (83.3% [274/329]) of patients experienced freedom from symptomatic atrial recurrence through 12 months. Of the 70 documented recurrences, 34 (49%) were documented by trans-telephonic monitoring only. All domains captured on the AFEQT questionnaire showed improvement with the overall score improving by 25.7, which exceeded the threshold of clinically meaningful improvement (±5) (Table). Patient reported most improvements in PAF control and symptoms relieved. The overall AFEQT score improvement was seen both in patients with or without documented atrial arrhythmia recurrence, with improvement by 21.5 and 26.8, respectively. Conclusion: PAF ablation using a standardized CLOSE workflow resulted in consistent improvements in QoL. The improved QoL was observed regardless of atrial arrhythmia recurrence likely reflecting the low residual arrhythmia burden in patients with documented recurrence identified only on TTM.